Cuidados paliativos e espiritualidade: um estudo com enfermeiros - Evangelista, Carla Braz (2015)
Palliative care is an approach that improves the quality of life of patients and family members facing life-threatening diseases through the relief of physical, psychological and spiritual suffering. Therefore, it is observed that spirituality helps patients face difficult situations and is considered an important tool in palliative care, to ease the suffering and pain caused by terminal and chronic degenerative diseases. This master´s degree thesis was consisted of two articles: the first is called Palliative Care and Spirituality: an integrative literature review, and aimed to analyze scientific articles produced worldwide on palliative care and spirituality: through an integrative review. The research corpus is consisted of 40 articles published from 2005 to 2014, in the LILACS, MEDLINE and IBECS and SciELO databases. From textual analysis of the publications four thematic approaches have emerged: AT I - The meaning of spirituality in the context of palliative care; AT II – Palliative care and spiritual assistance; AT III – Spirituality, pain relief and other symptoms that affect patients under palliative care, and AT IV -assessment tools of the spiritual dimension in the context of palliative care. The results indicate the importance of the spiritual dimension of patients under palliative care and the incipient production of articles about this theme nationwide, which makes it necessary to develop new studies to disseminate knowledge on the subject. The second, original, entitled "Spirituality as a therapeutic resource in palliative care: understanding nurses", and aims to understand how nurses employ spirituality as a therapeutic resource in assisting patients under palliative care and identify the influence of his belief and faith in assisting them. This is a qualitative field research, developed in a charity hospital that looks after cancer patients under palliative care, in the city of João Pessoa (PB). The sample consisted of 10 nurses. The research project was submitted to the Ethics Committee at the Health Sciences Centre, from which it received a certificate of approval, with CAAE registration under n. 32194614.2.0000.5188. Data were collected from August to October 2014 by applying semi-structured interviews and analyzed using content analysis technique. The analysis of the empirical material of the study allowed the construction of three categories: understanding palliative care and spirituality; spiritual needs of patients under palliative care; the influence of one’s belief and faith in the assistance of patients under palliative care. The nurses recognize the importance of the spiritual dimension in patient assistance under palliative care and seek to meet their needs using a variety of strategies based on this dimension.